Several ADP-ribosylation factor (Arf) isoforms support COPI vesicle formation* - Popoff, Vincent; Langer, Julian D.; Reckmann, Ingeborg; Hellwig, Andrea; Kahn, Richard A.; Brügger, Britta; Wieland, Felix T. (The journal of biological chemistry, 2011)
Newly synthesized proteins and lipids are transported in vesicular carriers along the secretory pathway. Arfs (ADP-ribosylation factors), a family of highly conserved GTPases within the Ras superfamily, control recruitment of molecular coats to membranes, the initial step of coated vesicle biogenesis. Arf1 and coatomer constitute the minimal cytosolic machinery leading to COPI vesicle formation from Golgi membranes. Although some functional redundancies have been suggested, other Arf isoforms have been poorly analyzed in this context. In this study, we found that Arf1, Arf4, and Arf5, but not Arf3 and Arf6, associate with COPI vesicles generated in vitro from Golgi membranes and purified cytosol. Using recombinant myristoylated proteins, we show that Arf1, Arf4, and Arf5 each support COPI vesicle formation individually. Unexpectedly, we found that Arf3 could also mediate vesicle biogenesis. However, Arf3 was excluded from the vesicle fraction in the presence of the other isoforms, highlighting a functional competition between the different Arf members.